Efektivitas Problem Based Learning terhadap Kemampuan Berpikir Kritis Mahasiswa - Muhamad Riyanto; Masduki Asbari; Dahru Latif (Journal of Information Systems and Management (JISMA), 2024)
This research aims to describe the application of problem based learning in an effort to develop students' critical thinking skills in Science Learning courses. One of the advantages of the problem based learning model is that it is able to train students to use various concepts, principles and skills that they have learned to solve the problems they are facing. By implementing problem based learning, critical thinking skills can develop, because the critical thinking skills observed in this research are the ability to identify, analyze, solve problems, think logically, make appropriate decisions, not be easily manipulated and draw conclusions, and not be easily deceived. . A way of thinking that is clear and rational, open, and based on evidence and facts regarding what we read, hear or see.